Blended Way of Learning in Early Years: Approaching an Era of Unified Opportunities in Learning - CHANDRA, Reetu (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2023)
The pandemic's effects on young children's learning and development were felt globally, affecting children across countries and continents as a result of school closures. Governments increased their efforts to bridge the digital gap and made it possible to guarantee that children acquired fundamental skills. Lessons learned from the epidemic helped people understand the advantages of digital learning and encouraged the careful use of digital learning with more traditional learning methods. The best way to address gaps in reading and numeracy, especially those brought on by learning interruptions, is to adopt blended learning techniques with young children at an early stage of their learning and development. This paper is a literature review that thrives on understanding the significance of blended learning for young children, emerging challenges in its adaptation, and contemporary ways for its better adaptation. The creation of an enabling digital learning environment, customization of curriculum and learning material, ensuring continuous assessment of children, building understanding of blended learning among teachers and parents, lack of access to digital devices and connectivity, access to unregulated multiple learning resources, and the expensive nature of implementation of blended learning are the major challenges upfront. However, concerted efforts in adjusting the learning environment, curriculum, and pedagogical processes for blended learning, building competency of teachers, parents, and children on the use of blended modes, ensuring reliable and regulated digital platforms, bringing in administrative and systemic reforms, ensuring resource support, and increasing additional fund allocation are some of the trending steps for smooth positioning of blended learning in the education of young children.